ON THE ISSUE OF APPLICABILITY OF THE TERM «BRACKISH LAGOON» TO WATER BODIES ON THE TERRITORY OF THE KRASNODAR KRAY - Nikita M. Zheleznyak (Водное хозяйство России: проблемы, технологии, управление)
The article discusses the issues of water bodies typification in the territory of the Krasnodar Kray. In this regard, it is determined that the geographical names of water bodies in the region often do not coincide with their type in the modern sense. The main problems related to the typification of water bodies are identified: difficulties in determining the authorized body for granting rights to use the waters of “estuaries (“brackish lagoon”), determining their coastline, parameters of water protection zones and establishing these zones on the ground, dividing the responsibilities of regulatory authorities, etc. The issue of formation of estuaries (brackish lagoons) on the territory of the Krasnodar Kray is considered. The main characteristics of the estuaries’ flora and fauna are described. Recommendations for typifying a number of water bodies in the Krasnodar territory are given. It is proposed to divide objects currently belonging to the “estuary” (brackish lagoon) type into “lakes”, “lakes of lagoon origin”, and “estuaries” proper.